PENGARUH INOKULASI CENDAWAN MIKORIZA ARBUSKULA (CMA) DAN BERBAGAI TARAF PUPUK P TERHADAP KADAR P DAUN DAN KUALITAS BmIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN PENDAHULUAN - Eko Sulistyono; M. H. Bintoro Djoefrie; Ismantiri Heningtyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
Glasshouse experiment was conducted to study the effect of mycorrhizae inoculation and it's interaction with P supply on P leaf content and quality of oil palm seedling. Factorial experiment was arranged in Randomized Block Design with three replications. The first factor were mycorrhizae inoculation : without inoculation, mixed mycorrhizae, Acaulospora sp, Glomus manihotis, Glomus sp.1, Glomus sp. 2, Glomus sp. 3, The second factor were level of Roch Phosphate fertilizer : 0 g/seedling, 2 g/seedling, 4 g/seedling and 6 g/seedling. Mycorrhizae inoculation affected the P leaf content and percentage of infection significantly, Glomus sp decreased P leaf content. Acaulospora sp. gave the best quality of seedling, but Glomus sp. 3 gave the bad one. The Rock Phosphate application did not affect on P leaf content absorption efficiency and inoculation percentage due to high soil phosphorus content.